Review: The Efficacy of Several Agricultural Wastes as Ameliorant for Peat Degraded Soil: The Case of Kalimantan - Fatimah, Siti; Noor, Muhammad; Saputra, Riza Adrianoor (TROPICAL WETLAND JOURNAL, 2024)
Various agricultural wastes are used as ameliorants to improve degraded peat soils, with a focus on cases in Kalimantan. Peat soil is one of the potential land resources for agriculture in Indonesia, with an area ranging from 12.59 to 14.90 million ha, spread across Kalimantan, Sumatra, and Papua. However, the use of peat soil for agriculture faces many obstacles, such as low pH, low base saturation, organic acid toxicity, and macro- and micronutrient deficiencies. The use of agricultural waste as an ameliorant to improve degraded peat soil has prospects and opportunities. Agricultural waste is rich in nutrients and, if managed well, can contribute to sustainable agriculture. This review outlines the characteristics and potential of various agricultural wastes, such as animal waste, food processing waste, crop residues, and hazardous agricultural waste. These wastes are abundantly available and cost-effective, making them a valuable resource for increasing soil fertility and crop yields. This review provides insight into the application of agricultural waste as an ameliorant for degraded peat soils in Kalimantan and identifies challenges and opportunities in this context. This information is important in enriching future peatland management strategies in relation to increasing productivity and production of cultivated plants on peatlands.